THE PHENOMENON OF EARLY MARRIAGE: POLICY ANALYSIS OF THE BELOPA RELIGIOUS COURT OF LUWU REGENCY - Akbar, Muhammad (MIZAN: JOURNAL OF ISLAMIC LAW, 2023)
The rise of early marriages in Belopa, Luwu Regency, has increased every year. Therefore, the purpose of this research is to find out the performance of the Belopa Religious Court in addressing and presenting a marriage dispensation policy and knowing the perspective of Islamic law with the widespread early marriage in Belopa. This type of research is field research and exploratory. The research informants consisted of 6 husband and wife couples, 3 parents or marriage guardians, head of KUA, 1 KUA employee, 2 judges, 2 clerks and 1 employee of the Belopa Religious Court. Research data obtained by means of observation, in-depth interviews and documentation. Furthermore, the data were analyzed by descriptive qualitative. The results of the study show that the performance of the Belopa Religious Court in addressing and presenting the marriage dispensation policy in the fairly easy category is given with evidence that the majority of marriage dispensation applications submitted at the Religious Courts are granted by the judge. Beside from that, this research also illustrates that Islamic Law as a mitigation patron for the rise of early marriage can be effective if it is not permissible to ignore the Marriage Law Number 16 of 2019 where when fiqh has been transformed into law then actually fiqh products which are the source of material must be seen as not is no longer valid or at least the product is no longer binding. Our only reference is the law with all the regulations under it.